The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4161/hv.28578
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination strategies for Parkinson disease

Abstract: Parkinson disease is the second most common neurodegenerative disease in the world, but there is currently no available cure for it. Current treatments only alleviate some of the symptoms for a few years, but they become ineffective in the long run and do not stop the disease. Therefore it is of outmost importance to develop therapeutic strategies that can prevent, stop, or cure Parkinson disease. A very promising target for these therapies is the peripheral immune system due to its probable involvement in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 197 publications
(212 reference statements)
0
9
0
Order By: Relevance
“…We have shown that allelic variance of Mhc2ta related to lower expression MHCII levels resulted in increased a-syn toxicity in rats that correlated with a higher microglia response ( Jimenez-Ferrer et al, 2017 ), thus suggesting that a failure in the adaptive immune signal (MHCII-CD4 T cell) will have consequences in the neuronal survival to a-syn insult. In PD patients the CD4 population seems to be altered ( Fiszer et al, 1994 ; Saunders et al, 2012 ; Stevens et al, 2012 ) and they seem to be more prone to apoptosis, and differ in their activation state, which could suggest that a failure of the CD4 cells response might be happening in PD ( Romero-Ramos et al, 2014 ). However, we should also consider a differential response of the T-cells to the different types of a-syn presented through the disease, thus changing the nature of their response as disease progress.…”
Section: Cascades Initiated By Alpha-synuclein In Microgliamentioning
confidence: 99%
“…We have shown that allelic variance of Mhc2ta related to lower expression MHCII levels resulted in increased a-syn toxicity in rats that correlated with a higher microglia response ( Jimenez-Ferrer et al, 2017 ), thus suggesting that a failure in the adaptive immune signal (MHCII-CD4 T cell) will have consequences in the neuronal survival to a-syn insult. In PD patients the CD4 population seems to be altered ( Fiszer et al, 1994 ; Saunders et al, 2012 ; Stevens et al, 2012 ) and they seem to be more prone to apoptosis, and differ in their activation state, which could suggest that a failure of the CD4 cells response might be happening in PD ( Romero-Ramos et al, 2014 ). However, we should also consider a differential response of the T-cells to the different types of a-syn presented through the disease, thus changing the nature of their response as disease progress.…”
Section: Cascades Initiated By Alpha-synuclein In Microgliamentioning
confidence: 99%
“…Targeting the immune system and using immunotherapy are promising strategies for treating PD [ 86 ]. Immunotherapy holds the key to be the one of the disease-modifying strategies against PD, as immunizing patients in their early stages and prior to the accumulation of α-syn deposits would be the most effective strategy in preventing the progression of the disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As α-syn aggregates are the target of immunotherapy trials in PD, an important consideration and possible side effect is the induction of inflammatory autoimmunity mediated by Th17 cells (subset of T helper cells) as α-syn is an endogenous self-protein and Th17 cells have been shown to be involved in the neurodegenerative neuroinflammatory process [ 86, 88 ]. No study using antibodies to induce protection in PD models have studied the T cell response [ 86 ]. Therefore for immunotherapy against α-syn to be an effective treatment, it must consider the adaptive immune response to regulate the response against α-syn and immunotherapy must be initiated prior to the formation of α-syn aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) is a neurotoxin drug of MPP+, which causes permanent symptoms of PD by destroying dopaminergic neurons in the substantia nigra of the brain for mouse modeling [65]. PD01A is a Phase 1 epitope vaccine in experimental -a synthetic a-syn mimicking peptide-polymer based on a-syn aggregate by inducing an immune response that generates antibodies specifically against it [66]. In general, vaccines are developed according to the T cell response, but a peptide epitope with a three-celled peptide epitope with a three-cell universal peptide such as Syn85-99 (AGSIAAATGFVKKDD), α-Syn109-126 (QEGILEDMPVDPDNEAYE), α-Syn126-140 (EMPSEEGYQDYEPEA) and P30 (FNNFTVSFWLRVPKVSASHLE) epitope vaccines comprising three peptide-based epitope vaccines comprising different α-Syn peptides, but consisting of different B cell epitopes as follows, are noted for their high immunogenicity [67].…”
Section: Current Situation and Future Perspectivementioning
confidence: 99%